Частоти мутації 5382INSC гена BRCA1 у жінок, хворих на рак молочної залози, в трьох областях України - Городецька, Є.В.; Серга, С.В.; Лагута, Т.І.; Левкович, Н.М.; Анікусько, М.Ф.; Тимовська, Ю.О.; Чешук, В.Є.; Смоланка, І.І.; Скляр, С.Ю.; Поленков, С.Е.; Бойченко, О.І.; Демидов, С.В.; et al. (Фактори експериментальної еволюції організмів, 2015)
Aims. Breast cancer ranks first among cancers of the female population in Ukraine and in most countries abroad. However, data on the mutations frequencies in Ukraine for BRCA1 gene is limited. We investigated the variation and frequency of mutations in gene BRCA1 among patients with breast cancer in three regions of Ukraine. Methods. Mutation 5382insC was screened by PCR using specific primers as described in Negură L., et al., 2010, with some optimization. Results. In total, we screened 155 breast cancer patients for the 5382insC mutation. Nine BRCA1 mutations 5382insC were detected (5.8 ± 1.87 %). The study was conducted in Kyiv region (104 patients, including 7 with mutation), Chernihiv region (13 patients, 1 with mutation) and Zhytomyr region (38 patients, 1 with mutation). Conclusions. Frequencies of 5382insC did not differ between three regions and from the data obtained by our colleagues in Donetsk, Lviv and Chernivtsi regions. Keywords: BRCA1, 5382insC, mutation, Ukraine.